Anthropogenic threats to resident and dispersing African wild dogs west and south of the Kruger National Park, South Africa,Antropogenic threats to resident and dispersing African wild dogs west and south of the Kruger National Park, South Africa - Watermeyer, Jessica Patricia (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2012)
African wild dog Lycaon pictus populations are declining and the species is listed as Endangered by the IUCN. The Kruger National Park (KNP) is home to the only viable population of wild dogs in South Africa, but census results reveal consistently low numbers since the late 1990s. Wild dogs display wide-ranging behaviour and it is possible that the species might frequently use unprotected lands adjacent to the KNP. However, very little is known about wild dog movements beyond the boundaries of the KNP, and whether or not adjacent land owners are tolerant of the species. Significantly, threats along the boundaries may have negative consequences for the KNP population. This research investigated the dispersal habits of wild dogs beyond the western and southern boundaries of the KNP, and gathered information on human tolerance, and anthropogenic threats in an area of mixed land use. The land west of the KNP presented the best prospect for wild dog range expansion. The wild dog packs operating outside the KNP had smaller home ranges and less home range overlap than the packs operating within the KNP. In addition, my data suggested that the development of conservancies and the formation of ecotourism-based land use practices would be beneficial for wild dog conservation. Failed wild dog dispersals due to snaring and human persecution could threaten the genetic stability and persistence of the KNP population. Therefore, raising awareness and an understanding of the plight of wild dogs is important for improving land owner perception and tolerance outside of protected areas. The rapidly increasing human population continues to infringe on protected lands and fragment landscapes, thus cooperation from individual land owners is vital for the conservation of free-ranging large carnivores.
Keywords: African wild dog -- South Africa -- Kruger National Park; African wild dog -- Effect of human beings on -- South Africa -- Kruger National Park; African wild dog -- Behavior -- South Africa -- Kruger National Park; Endangered species -- South Africa -- Kruger National Park; African wild dog -- Dispersal -- South Africa -- Kruger National Park; African wild dog -- Conservation -- South Africa -- Kruger National Park; Animal populations -- Estimates -- South Africa -- Kruger National Park